Censorship: Slowdown (Kazakhstan) - Voidly (2024)
WARNING severity censorship detected in Kazakhstan. Confidence: 75%. Data sourced from CensoredPlanet.
Censorship Incident ID: KZ-2024-0003
Keywords: censorship; KZ; censorship; warning